Characterizing infections in prosthetic breast reconstruction: A validity assessment of national health databases. Issue 10 (October 2017) - Piper, Merisa L.; Roussel, Lauren O.; Koltz, Peter F.; Wang, Frederick; Singh, Kyra; Chin, Robin; Sbitany, Hani; Langstein, Howard N.
Summary: Introduction: Current guidelines in the United States require reporting only the 30-day postoperative outcomes to standardized databases, including the National Surgical Quality Improvement Program (NSQIP). Thus, many breast implant-related complications go unreported in standard databases. We sought to characterize late periprosthetic infections following implant-based breast reconstruction. Methods: We conducted a retrospective analysis of all women who underwent expander/implant reconstruction from 2005 to 2014 at two institutions. All periprosthetic infections were identified and divided into early and late cohorts (≤30 days or >30 days). Infection was defined as any episode where antibiotics were initiated or a prosthetic device was explanted because of clinical evidence of the infection. Results: In the 1820 patients (2980 breasts) identified, 421 periprosthetic infections occurred (14%). Of these, 173 (41%) were early and 248 (59%) were late (mean time to infection = 66.4 ± 101.9 days). Patients with late infections were more likely to be current smokers or have diabetes than patients with early infections (p < 0.034 for both). Infections caused by gram-negative bacteria and antimicrobial-resistant strains of Staphylococcus were more common in the early infection group (p < 0.001 for both). Implant loss due to infection was more common in the late infection group (p = 0.037). Discussion: Late periprosthetic infections following implant-based breast reconstruction are underestimated in national outcome databases and have unique risk factors and microbiology compared to early infections. A system-level change in reevaluating and redefining a timeline for tracking and treating implant infections is necessary, given the substantial morbidity associated with, and frequency of, late periprosthetic infections.